Synthesis and characterization of the polystyrene - asphaltene graft copolymer by FT-IR spectroscopy - León Bermúdez, Adan Yovani; Salazar, Ramiro (CT&F - Ciencia, Tecnología y Futuro, 2008)
The creation of new polymer compounds to be added to asphalt has drawn considerable attention because these substances have succeeded in modifying the asphalt rheologic characteristics and physical properties for the enhancement of its behavior during the time of use. This work explains the synthesis of a new graft copolymer based on an asphalt fraction called asphaltene, modified with maleic anhydride. Polystyrene functionalization is conducted in a parallel fashion in order to obtain polybenzylamine resin with an amine - NH2 free group, that reacts with the anhydride graft groups in the asphaltene, thus obtaining the new Polystyrene/Asphaltene graft copolymer.